Maritime Potencies in Quranic Perspective and the Role of Indonesian Youth - Serli Roisca (Institut Agama Islam Negeri (IAIN) Curup, 2018)
Drawing the concept of the sea through the perspective of the Qur'an needs to be done, so that people know how to manage, explore, and utilize the sea. Therefore, for the purposes of exploration is required exploratory methods are balanced and proportional to avoid the occurrence of sea damage and its contents. Positioning sea exploration as one a common platform in the economic development of Indonesia, it seems that it is not only a feasible solution for the Indonesian people to rise from the crisis. Thus, they will gain prosperity and happiness in their lives. Islamic Idealism requires that the issue be restored and resolved based on the teachings contained in the Qur'an and Sunnah. So, the Qur'an serves as a guide for life and human life has been very clear exposes the potential of marine. Alqur'an has clearly exposed so potential mankind in the utilization of natural resources, especially marine resources. Young Indonesians proclaimed to be demographic bonuses in 2020 are the nation's assets and future generations that must be able to maintain the work ethic of the sea as the embodiment of maritime culture that is still attached. The working ethos of the sea should be ingrained in the life of the youth as the generation of the nation so that the next 50 to 100 years of progress will remain intact. Therefore, improving the quality of youth especially with regard to the utilization of marine potential is very important to be done through maritime culture as a nation culture that should always be invested as the main pillar of youth development of Indonesia.